THERMAL ACTIVATION OF PLUMS - Usmonova, Zulfiya (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2025)
The activation process by thermal pyrolysis is critical in producing carbonaceous adsorbents based on local food waste. This article describes the initial pyrolysis and carbonization processes for obtaining activated carbons with high adsorption properties from plum pits. The research methods were carried out based on examples presented in the literature, test results obtained on devices that meet the requirements of world standards, and GOST standard indicators. It also allows understanding the mechanisms of optimal conditions for converting biomass-based food waste into valuable adsorbent material.